2007
DOI: 10.1111/j.1532-5415.2007.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Patients with Dementia: How Good Is the Quality of Care? Results from Three Health Systems

Abstract: In general, dementia care quality has considerable room for improvement. Although greater comorbidity and dementia severity were associated with better quality, caregiver knowledge was the most consistent caregiver characteristic associated with better adherence. These findings offer opportunities for targeting low quality and suggest potential focused interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 37 publications
3
80
0
2
Order By: Relevance
“…48 Previous research comparing people from older age groups, with and without dementia, has shown dementia to be independently associated with poor quality of care. [24][25][26][27] The findings of association between the quality of care and greater number of comorbid medical conditions and medications may be due to increased likelihood of attendance to consultations. 15,24 Comparison with existing literature The deficiencies in the quality of care received by people with dementia are consistent with previous studies demonstrating suboptimal care received by these patients in secondary and private care settings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…48 Previous research comparing people from older age groups, with and without dementia, has shown dementia to be independently associated with poor quality of care. [24][25][26][27] The findings of association between the quality of care and greater number of comorbid medical conditions and medications may be due to increased likelihood of attendance to consultations. 15,24 Comparison with existing literature The deficiencies in the quality of care received by people with dementia are consistent with previous studies demonstrating suboptimal care received by these patients in secondary and private care settings.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…[24][25][26][27] The findings of association between the quality of care and greater number of comorbid medical conditions and medications may be due to increased likelihood of attendance to consultations. 15,24 Comparison with existing literature The deficiencies in the quality of care received by people with dementia are consistent with previous studies demonstrating suboptimal care received by these patients in secondary and private care settings. [24][25][26][27] Although improved performance in care for individual conditions like diabetes has been apparent in recent years -and since the introduction of the QOF in UK general practice 49,50 -this is not necessarily true for all subgroups of patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality criteria have either been defined as expert standards (Chodosh et al 2007) or the outcome variables of studies of family caregiver interventions (for example reduction of caregiver's burden) are regarded as quality criteria (Mahoney et al 2001). To date, there are no empirical studies of the various characteristics of caregiver counselling regarding their effectiveness, although specific characteristics, such as counselling about the various forms of dementia appear sensible and necessary (Ibach et al 2004).…”
Section: Structural Quality (S): Non-personal Factors (S I); Person-rmentioning
confidence: 99%